PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK PADA MATERI SPLDV BERBASIS KEARIFAN LOKAL MAUPONGGO UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA - Coo Bule, Modesta Venidora (Lembaga PKBM Tunas Harapan Varoso, 2024)
The aim of this research is to develop student worksheets based on Mauponggo local wisdom to improve mathematical problem solving abilities at SPLDV. This type of research is development research (R&D). The development of this student worksheet uses the ADDIE development model, namely: Analysis (A), Design (D), Development (D), Implementation (I), Evaluation (E). Implementation of the use of student worksheets based on Mauponggo local wisdom in learning mathematics on SPLDV material through the classroom action research stage, which was carried out directly by intern students at SMA Negeri 1 Mauponggo which was carried out in 2 cycles. The results of the mathematics learning test in cycle I were 1 student or 3.03% completed and 32 students or 96.96% incomplete. The results of the mathematics learning test in cycle II showed that 17 students or 51.51% had completed it and 16 students or 48.48% had not completed it. This shows that this student worksheet is practical for use in learning mathematics. Thus, this student worksheet meets the criteria, is practical, and is effectively used in improving mathematical problem solving abilities.